Shrinking City Phenomenon in a Small City at East Coast Area of North Sumatra - Mardianta, Anthoni Veery; Zahrah, Wahyuni; Marpaung, B O Y; Nathasya; Dewi, Citra; Siregar, Cindy (International Journal of Architecture and Urbanism, 2025)
City dynamics must be seen as a complex system with varying degrees of non-linear interaction of space and time. Cities are not constantly growing. At some point it will shrink and may die. Many factors cause such as globalization, suburbanization, post-socialism, and changes in demographic structure and so on. In many studies, the shrinking city phenomenon is mostly carried out in developed countries. However, developing countries are not impossible to experience this phenomenon. Each city experiencing the shrinking city phenomenon has different characteristics. In developing countries, local government policies that depend on various aspects of central government policies have a level of vulnerability to shrinking city phenomenon. Changes in central government policy on the smal city have an impact on changes in the economic structure of the city. Moreover, limited resources and the absence of small city innovation make it increasingly difficult for cities to grow.